Analisis Dinamika Model Penyakit Toksoplasmosis pada Populasi Kucing dan Manusia - Riza Rusdiani; Ali Kusnanto; Paian Sianturi (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
Abstract: Toxoplasmosis is a disease that is identical to cats. This disease is caused by the parasite Toxoplasma gondii. In this study, a mathematical model of the spread of toxoplasmosis was reviewed with various population size. In this study, model construction, fixed point analysis and parameter sensitivity analysis were carried out. From the sensitivity analysis, it is shown that the cat transmission rate from a susceptible cat population to an infected cat population (horizontal transmission rate) and the probability of a susceptible cat born from an infected cat (vertical transmission rate) are found as sensitive parameters on production number ( Decreasing the horizontal transmission rate and an increase value of the vertical transmission rate can reduce the value of A decrease in the value of , results in a disease-free state will be achieved more quickly so that the disease is under control.